The use of exit tickets and learning journals in promoting reflection in young EFL learners - Suharto, Pipit Prihartanti; Damayanti, Ika Lestari; Lengkanawati, Nenden Sri (EduLite: Journal of English Education, Literature and Culture, 2025)
Exit tickets and learning journals are classroom tools that prompt end-of-lesson reflection. Exit tickets are brief, low-stakes prompts completed at lesson close to recall key ideas and self-evaluate; learning journals provide short written space across lessons for reflection and simple goal setting. This study examines how these tools facilitate self-reflection and relate to early signs of metacognitive self-regulation and learner autonomy among young Indonesian EFL learners. A qualitative-dominant, embedded mixed-methods design within a participatory action research (PAR) framework was implemented in a primary EFL classroom. Data comprised student written reflections (exit tickets, learning journals), classroom field notes, and participation/completion records; simple descriptive counts supported the qualitative analysis. The tools were treated as metacognitive prompts for planning, monitoring, and evaluating. Findings show that exit tickets promoted immediate, end-of-lesson reflection and were easier for students to complete, whereas learning journals supported self-assessment and short goal setting across lessons. Reflection depth was often uneven, influenced by task complexity, linguistic load, and unfamiliarity with terms or platforms; field notes recorded confusion when instructions were unclear, and engagement dipped during an asynchronous session. Repeated use fostered procedural self-regulation, evidenced by faster, more independent completion. Implications include using short, clear, visual prompts with brief modeling, simplifying journal templates, and aligning prompts tightly with lesson content to deepen reflection and strengthen early autonomy in Indonesian EFL classrooms.